Tradisi Uang Pelangkah Pernikahan Dalam Adat Betawi di Tinjau Dari Hukum Islam di Kecamatan Babelan Kabupaten Bekasi - Kusuma, Indra Wijaya; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
Marriage is a physical and mental bond between a man and a woman as husband and wifewith the aim of forming a happy and eternal family or household based on the Supreme Lordship.In the custom of marriage in the people of Babelan District, Bekasi Regency, there is a customthat if someone wants to get married but there is an older brother who is not married, then thatperson must wait for his brother to marry first or can marry before his brother on condition that theperson who wants to step over his brother must give something in the form of money or goods to herbrother. According to traditional leaders, the stepper is required to maintain a good relationship withhis brother. However, if the stepper was burdensome or prevented his younger sibling from gettingmarried, the traditional leader revealed that this was not justified because the stepper could not beasked for a certain nominal value or certain items, only the awareness of his younger sibling. Inline with the opinion of traditional leaders, clerical figures reveal that stepping may be applied onthe basis of the rules of Ø§Ù„Ø¹Ø§Ø¯Ø© Ù…ÙØÙŽÙƒÙŽÙ‘Ù…Ø© , but this is not a necessity.. Primary data sources were obtainedfrom interviews and secondary data sources were obtained from books, magazines, journals, etc.The type of research used in this research is the type of field research (Field Research). The researchapproach carried out by the author uses descriptive qualitative. Data collection is done by theauthor to get and understand the picture and the existing reality, the writer uses data collectiontechniques by interview, observation and documents. From the data that has been collected, then thewriter analyzes using descriptive method. Based on the research data, the authors conclude that thetradition of stepping marriage money can be preserved because the tradition of stepping marriagemoney is not only a symbol of national identity, but also as a form of respect for older siblings whowill be stepped over and as a guardian of good family relations. Although it must be preserved, theremust be filtering and adjustments to fiqh so that there is no conflict between adat and fiqh. Some ofthe problems with stepping customs that must be filtered and adapted to fiqh include the prohibitionof marriage from older siblings to younger siblings who wish to marry. Barring his younger siblingfrom marrying is not justified in custom and in fiqh it can be forbidden because it can cause a lotof harm. In addition, things that are burdensome and troublesome for a person to get married mustalso be eliminated. The brother who is going to be stepped over must be able to accept whatever theyounger siblings give as a permit application to marry. Should not impose the ability of the youngersibling and must not burden the request of the younger sibling.